Poa annua: An annual species? - Carroll, Devon E.; Horvath, Brandon J.; Prorock, Michael; Trigiano, Robert N.; Shekoofa, Avat; Mueller, Thomas C.; Brosnan, James T. (PloS one, 2022)
As the Latin name annua implies, the species Poa annua L. is thought to have an annual life cycle. Yet, there are many reports in literature of P . annua persisting as a perennial. Considering that P . annua senescence patterns do not align with other true annual species, we hypothesized that P . annua is similar to other perennial, C 3 turfgrass species that are subject to a confluence of environmental factors that can cause mortality. Four experiments were conducted in Knoxville, TN with the objective of determining environmental factors lethal to P . annua . A field monitoring study assessed 100 P . annua plants across ten grassland micro-environments from May to October 2020. Forty plants survived the summer and confirmed the existence of perennial P . annua ecotypes. Analysis of environmental factors at the time of plant death indicated soil moisture, soil temperature, and pathogenic infection were associated with mortality. A series of glasshouse or field experiments were conducted to investigate the effects of each factor on P . annua mortality. Soil moisture and soil temperature were not lethal to P . annua in the glasshouse, except under extreme conditions not typical in the field. A field study assessed mortality of plants from pathogenic infection and indicated that P . annua plants treated with fungicide throughout the summer survived year-round, whereas plants not receiving fungicide applications senesced. These findings support our hypothesis that P . annua is of a perennial life cycle, which can be influenced by environmental conditions. We suggest that the name P . annua is likely a misnomer based on its modern interpretation.